Mechanochemical synthesis of poly(trimethylene carbonate)s: an example of rate acceleration - Park, Sora; Kim, Jeung Gon (Beilstein Journal of Organic Chemistry, 2019)
Mechanochemical polymerization is a rapidly growing area and a number of polymeric materials can now be obtained through green mechanochemical synthesis. In addition to the general merits of mechanochemistry, such as being solvent-free and resulting in high conversions, we herein explore rate acceleration under ball-milling conditions while the conventional solution-state synthesis suffer from low reactivity. The solvent-free mechanochemical polymerization of trimethylene carbonate using the organocatalysts 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) are examined herein. The polymerizations under ball-milling conditions exhibited significant rate enhancements compared to polymerizations in solution. A number of milling parameters were evaluated for the ball-milling polymerization. Temperature increases due to ball collisions and exothermic energy output did not affect the polymerization rate significantly and the initial mixing speed was important for chain-length control. Liquid-assisted grinding was applied for the synthesis of high molecular weight polymers, but it failed to protect the polymer chain from mechanical degradation.
Keywords: aliphatic polycarbonate; green polymerization; mechanochemistry; organocatalyst; poly(trimethylene carbonate)